2009
DOI: 10.1007/s10764-009-9375-9
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Multifemale Social Organization in a Group of Nomascus concolor at Wuliang Mountain, Yunnan, China

Abstract: Many short-term studies have reported groups of black crested gibbons containing ≥2 adult females (Nomascus concolor). We report the stability of multifemale groups in this species over a period of 6 yr. Our focal group and 2 neighboring groups included 2 breeding females between March 2003 and June 2009. We also habituated 1 multifemale group to observers and present detailed information concerning their social relationships over a 9-mo observation period. We investigated interindividual distances and agonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 27 publications
4
45
2
Order By: Relevance
“…This differs from previous research, which reported that two females maintained similar spatial distance from the adult male in the neighboring group (Fan & Jiang, 2009). This variance may be due to different analysis methods as we defined 1 m as a proximity distance while Fan & Jiang (2009) used mean spatial distance for measuring the relationship. Considering the group history and different reproductive status of the two females (infant-carrying or not), we can give two possible explanations for our results.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This differs from previous research, which reported that two females maintained similar spatial distance from the adult male in the neighboring group (Fan & Jiang, 2009). This variance may be due to different analysis methods as we defined 1 m as a proximity distance while Fan & Jiang (2009) used mean spatial distance for measuring the relationship. Considering the group history and different reproductive status of the two females (infant-carrying or not), we can give two possible explanations for our results.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the proximity association between different individuals was uneven. Only ten dyads exhibited preferred proximity, and the sub-adult (SAM2) obviously exhibited peripheral clustering in the study group, as has been shown in previous research (Fan & Jiang, 2009). Four clustering units were identified and kinship was a good explanation for the observed pattern (Furuichi, 1984;Matsumura & Okamoto, 1997), as females preferred to keep proximity with offspring.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Dooley and Judge (2007) showed, however, that duet calls were important in intergroup communication. Territorial disputes are probably similar to those described for N. concolor (Fan and Jiang 2010;Fan et al 2007 and N. hainanus (Zhou et al 2008a).…”
Section: Ecologysupporting
confidence: 68%
“…In N. concolor, polygyny has been demonstrated by close observation of a group with 1 adult male and 2 adult females over 6 years, during which time both females gave birth (Fan and Jiang 2010). The authors suggest that this arose from unusual ecological and social circumstances: a large territory that provided adequate resources for the females and their offspring, and no other groups present (Fan and Jiang 2010).…”
Section: Behaviormentioning
confidence: 99%